Electric Fields and Surface Fermi Level in Undoped GaN/AlN Two‐Dimensional Hole Gas Heterostructures. Issue 4 (18th February 2021) - Janicki, Łukasz; Chaudhuri, Reet; Bader, Samuel James; Xing, Huili Grace; Jena, Debdeep; Kudrawiec, Robert
Abstract : Undoped GaN/AlN heterostructures with a high‐density 2D hole gas (2DHG) have recently been reported, demonstrating that holes can be generated in GaN without magnesium (Mg) doping. The presence of the high‐density 2DHG in these GaN/AlN heterostructures is expected to result from huge internal polarization fields. Herein, modulation spectroscopy is applied to analyze the built‐in electric fields in the top GaN layer of molecular beam epitaxy (MBE)‐grown GaN/AlN heterostructures with a buried 2DHG using contactless electroreflectance (CER). Experimentally obtained electric field values are compared with self‐consistent Schrödinger–Poisson energy band calculations of the GaN/AlN structures. This coupled experimental and theoretical analysis determines that the Fermi level at the GaN surface is located at ≈1.9 above the valence band (i.e., roughly in the middle of the bandgap)—for structures with undoped and Mg‐doped GaN. Finally, the comparison of calculated 2DHG concentrations in the structures under study with values determined from Hall effect measurements shows excellent agreement further strengthening the result. Abstract : Recently, the long missing undoped GaN/AlN 2D hole gas (2DHG) was discovered. Their optoelectronic properties are explored. Through the analysis of the built‐in electric field, the surface barrier height for holes is evaluated to be ≈1.9 eV.